2019
DOI: 10.3390/met9050553
|View full text |Cite
|
Sign up to set email alerts
|

On the Free-Surface Roughness in Incremental Forming of a Sheet Metal: A Study from the Perspective of ISF Strain, Surface Morphology, Post-Forming Properties, and Process Conditions

Abstract: Due to absence of any supporting die, the free surfaces in incremental sheet forming (ISF) experience uneven deformation. This results in rough surfaces, possibly leading to the reduced service life of components. Therefore, it is necessary to analyze and quantify the effects of the application of strain on the free-surface roughness. Moreover, in order to control roughness, both on the free surface and the opposite contact surface, the nature of correlation between the two types of roughnesses needs to be ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…More details will be discussed in the Section 4.1.3. Furthermore, compared with Ra values for monolithic sheets in Radu and Cristea [9], the roughness in single Al and SUS sheets are less than that in Al/SUS bimetal sheets (i.e., in the current study) which may indicate that the difference in the materials' strength of the bimetal sheets has an effect in increasing the surface roughness of latter sheets as confirmed in the recent study of Al-Ghamdi and Hussain [6]. As a result, there is a contradiction between the maximum forming angle and the surface roughness of bimetal sheets.…”
Section: Experimental Parameters Effectsupporting
confidence: 80%
See 1 more Smart Citation
“…More details will be discussed in the Section 4.1.3. Furthermore, compared with Ra values for monolithic sheets in Radu and Cristea [9], the roughness in single Al and SUS sheets are less than that in Al/SUS bimetal sheets (i.e., in the current study) which may indicate that the difference in the materials' strength of the bimetal sheets has an effect in increasing the surface roughness of latter sheets as confirmed in the recent study of Al-Ghamdi and Hussain [6]. As a result, there is a contradiction between the maximum forming angle and the surface roughness of bimetal sheets.…”
Section: Experimental Parameters Effectsupporting
confidence: 80%
“…Usually, this quality is defined with the average roughness value (Ra) and, to meet the requirements of the customers, the surface roughness of the produced desired parts should be within an acceptable range. The average surface roughness (Ra) is the most effective parameter that can be used to evaluate the quality of incrementally-formed parts since it gives information on the behavior of the contact and non-contact surfaces with the forming tool [6]. The main parameters that affect the contact surface roughness of a single-layer sheet are the step size, tool diameter, feed rate, and rotational speed [7].…”
mentioning
confidence: 99%
“…Powers et al [12] found that the maximum height of the profile Rz is greater with rolling marks perpendicular to forming orientation. The surface roughness increases with the post-forming sheet strength, forming force, and residual stress, thereby showing that strain hardening has a direct influence on the roughness [13]. Furthermore, Al-Ghamdi and Hussain [13] found that the free-surface roughness and the contact-surface roughness are inversely related.…”
Section: Introductionmentioning
confidence: 97%
“…The surface roughness increases with the post-forming sheet strength, forming force, and residual stress, thereby showing that strain hardening has a direct influence on the roughness [13]. Furthermore, Al-Ghamdi and Hussain [13] found that the free-surface roughness and the contact-surface roughness are inversely related. Durante et al [14] investigated the effect of spindle speed on the average surface of pyramid frusta.…”
Section: Introductionmentioning
confidence: 97%
“…Although ISF has a very reasonable economic performance in small-lot production and is fine for manufacturing those elements which cannot be obtained using conventional sheet forming methods, several attempts have been made to use the forming technique in mass production [187][188][189]. There are many factors which influence the applicability of ISF and the accuracy of the parts thus formed [190][191][192][193][194]: tool path strategy, mechanical properties of the sheet metal (material anisotropy, ability to strain harden, elastic properties), the technological parameters (i.e., tool diameter, tool path strategy, depth value between two tool passages, tool rotational speed, friction conditions) and design parameters (geometry of the product, sheet thickness). One surface of the drawpiece in SPIF revealed small linear grooves as a result of the interaction of the tool tip with the workpiece (Figure 10).…”
Section: Introductionmentioning
confidence: 99%